Prevalence of Asthma and Its Association with Socioeconomic Status, Gender, and Consanguinity in Lahore, Pakistan - Dr. Najiya al- Arifa; Usman Bashir (Journal of Basic and Emerging Sciences, 2025)
This study mainly aimed to establish the burden of asthma and allergies in Lahore, Pakistan, and certain gender and socioeconomic inequalities. Data from asthma patients attending the major outpatient department in Lahore was collected through a cross-sectional study design. The study sample was made of women and men who had been clinically diagnosed with asthma. Data on socio-demographic attributes, lifestyle habits, familial environment, and economic situation were collected using structured interviews. The studies reveal that the prevalence is overwhelmingly biased to the gender axis, showing a worse outcome for females as compared to males. Apart from this, there is also an observed degree of relationship between the socioeconomic status and the severity of the asthma, as the members of the lower income class have reported more difficulty to cope up with the disease condition. It was concluded that there is need for undertaking appropriate public health measures and policies for the treatment of asthma belonging to the poor segments of the population. It is recommended and discussed that future investigations in this area should examine the relationship between asthma, including both environmental influences and the interrelated aspects of socioeconomic status.